Skidmore, G., "Strength in Weakness: writings by eighteenth-century Quaker women" - Lunn, Pam (Quaker studies, 2004)
Skidmore, G. (ed.), Strength in Weakness: writings by eighteenth-century Quaker women, Walnut Creek, CA:AltaMira Press, 2003. pp.187, 0 7591 0521 9, Paper,£14.95, $ 19.95.